Kualitas Pengajaran Dosen dan Motivasi Belajar Mahasiswa dengan Siklus ACE APOS - Ni Ketut Erawati (FPMIPA IKIP PGRI Bali, 2018)
This study aims to determine the level of motivation and perceptions of students on the quality of teaching lecturers who apply the cycle ADL (case study in real analysis). This research was conducted at IKIP PGRI Bali which amounted to 37 people. Data were collected by questionnaires consisting of a quality questionnaire of teaching and learning motivation. The collected data is then analyzed by using the ideal maximum score (MI) and ideal deviation (SI). Based on the calculation results can be obtained MI and SI for motivation data are respectively are 25 and 8,3. While MI and SI for teaching quality data are 37,5 and 12,5 respectively. Based on the data can be known average student's motivation level is 40,595. While the average quality of teaching lecturers obtained 63,027. Based on these results show that the perception of students on the quality of teaching lecturers is directly proportional to the level of student learning motivation. Based on the results obtained can be concluded that the level of student motivation and student perceptions of the quality of teaching lecturers are in very good category (case study on learning real analysis) with ADL cycle.